Ewangelia i ekonomia. Amerykańskie źródła etyki gospodarczej - Sójka, Jacek (Humaniora. Czasopismo Internetowe, 2025)
This article seeks to present original nineteenth-century American religious thought on the moral obligations of business – thought with a strong influence on the twentieth century. Associations with the theses of Max Weber and Richard Tawney on the birth of capitalism may be natural, for it is precisely this model Protestant business leader and his motivations that will be discussed, but also his moral assessment of the entire economic system. It will thus reveal an America in which religiosity and civic engagement are closely intertwined, with the result that business and entrepreneurship are always seen and evaluated from an ethical perspective in terms of the common good. Out of this spirit grows a scientific way of thinking about the economy in the form of economics, which is intended to serve social development and moral improvement.